2017
DOI: 10.1007/s11906-017-0781-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction in Mother and Offspring During Preeclampsia: Contributions from Latin-American Countries

Abstract: Pregnancy is a physiologically stressful condition that generates a series of functional adaptations by the cardiovascular system. The impact of pregnancy on this system persists from conception beyond birth. Recent evidence suggests that vascular changes associated with pregnancy complications, such as preeclampsia, affect the function of the maternal and offspring vascular systems, after delivery and into adult life. Since the vascular system contributes to systemic homeostasis, defective development or func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 199 publications
1
35
0
6
Order By: Relevance
“…Preeclampsia exhibits diverse clinical manifestations such as mild or severe, early onset (<34 weeks) or late onset (>34 weeks), or the presence or absence of intrauterine growth retardation ( Gilstrap and Ramin, 2002 ; Giachini et al, 2017 ). Accumulating evidence has shown that pathological features of preeclampsia involve a shallow trophoblast invasion and poor spiral artery remodeling, resulting in placental hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia exhibits diverse clinical manifestations such as mild or severe, early onset (<34 weeks) or late onset (>34 weeks), or the presence or absence of intrauterine growth retardation ( Gilstrap and Ramin, 2002 ; Giachini et al, 2017 ). Accumulating evidence has shown that pathological features of preeclampsia involve a shallow trophoblast invasion and poor spiral artery remodeling, resulting in placental hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Una de las teorías más aceptadas para la presentación de complicaciones hipertensivas en el embarazo, es la implantación insuficiente de las células del citotrofoblasto, que se infiltran en la porción decidual de las arterias espirales, pero no penetran en su segmento miometrial (14,15). Las arterias espirales, por lo tanto, no se transforman en canales vasculares de gran capacitancia, sino que se mantienen estrechas, lo que resulta en una disminución en el flujo placentario (16)(17)(18). y da como resultado una alta velocidad de perfusión en el espacio intervelloso, lo que genera estrés de cizallamiento en el trofoblasto (19,20).…”
Section: Fisiopatologíaunclassified
“…PE is a severe disease characterized by the presence of hypertension and proteinuria during the second and third trimester of gestation ( Steegers et al, 2010 ). PE affects approximately 2–8% of all pregnancies ( Ghosh et al, 2014 ) and is associated with substantially higher maternal and fetal morbidity and mortality worldwide, especially in Latin American countries where PE is one of the leading causes of maternal and fetal mortality ( Giachini et al, 2017 ).…”
Section: Oxidative Stress Maternal Obesity and Pregnancy Outcomesmentioning
confidence: 99%